Hidradenitis Suppurativa: Host-Microbe and Immune Pathogenesis Underlie Important Future Directions - Simon W. Jiang; Melodi Javid Whitley; Paula Mariottoni; Tarannum Jaleel; Amanda S. MacLeod (Elsevier, 2021)
Hidradenitis suppurativa (HS) is an inflammatory disease of the skin with a chronic, relapsing-remitting course. The pathogenesis of the disease is poorly understood and involves multiple factors, including genetics, environment, host-microbe interactions, and immune dysregulation. In particular, the composition of the cutaneous microbiome shifts as the disease progresses, although it is unclear whether this is a primary or secondary process. Trials with immunomodulatory therapy elucidate the role of specific immune pathways and cytokine signaling in disease mechanism, such as TNF-α, IL-1β, IL-12, IL-17, IL-23, and complement. Future studies should continue examining the causes of and contributing factors to microbial changes and immune dysregulation in HS pathogenesis.